New records of Encyrtidae (Hymenoptera: Chalcidoidea) from the Netherlands - George Japoshvili; Rudy Soethof (Journal of Insect Biodiversity and Systematics)
The present study includes the material collected from various localities across the Netherlands between 1998 and 2025. During our survey, the number of encyrtid species recorded in the Netherlands increased by 23. Additionally, five genera: Aphycoides Mercet, 1921, Mayrencyrtus Hincks, 1944, Rhopus Forster, 1856, Sectiliclava Hoffer, 1957 and Trjapitzinellus Viggiani, 1967 were documented for the first time. Thus, the total number of encyrtid species known from the country is now 146. The encyrtid wasp fauna documented in this study is primarily characteristic of the Western Palaearctic and broader Palaearctic regions. The discovery of several new records further emphasizes the need for ongoing surveys to fully understand the encyrtid fauna of this region.